PENGEMBANGAN BISNIS KOPERASI SYARIAH MELALUI PELATIHAN DAN PENDAMPINGAN PELAKSANAAN PRINSIP SYARIAH, DASAR MUAMALAH MALIYAH - Umaimah, Umaimah; Krishnawati, Wenti; Tumirin, Tumirin; suwarno, Suwarno; Aska, Ara Faridah Nur Sausan (Jurnal Pengabdian Masyarakat dan Lingkungan, 2023)
The purpose of this activity is to increase knowledge and compliance with sharia principles and develop cooperative business at Baitut Tamwil Muhammadiyah AL DAII. This activity program is supported by Semen Indonesia's Corporate Social Responsibility (CSR) program. The implementation of these activities is carried out by holding training and mentoring on sharia principles, basic training on muamalah Maliyah and DSN MUI fatwas according to Islamic principles. Sharia principles training activities were carried out on Wednesday, 24 August 2022. The Basic Muamalah Maliyah & DSN MUI Fatwa Training was carried out by involving 3 (three) members of Baitut Tamwil Muhammadiyah AL DAII which was organized by DSN MUI.